1989
DOI: 10.1037/0021-843x.98.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Self-structure in schizophrenia.

Abstract: This study used a set-theoretical model to construct self-perception structures and person-perception structures for 10 recently hospitalized schizophrenic patients, 10 nonschizophrenic patients recently hospitalized for depression, and 10 nonpsychiatric subjects. Overall self-perception structures were significantly less elaborated in the schizophrenic patients when compared with either the psychiatric or the nonpsychiatric comparison group. No comparable differences were found for measures taken from the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 12 publications
8
43
1
Order By: Relevance
“…Moreover, a number of researchers have shown the HICLAS approach to be related significantly to theoretically relevant variables (e.g. Robey et al, 1989;Haviland et al, 1994) and there is evidence for the structure of social selves in late adolescence (e.g. Rosenberg and Gara, 1985;Berzonsky and Neimeyer, 1988;Byrne and Shavelson, 1996); thus, these prior studies show evidence of construct validity.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, a number of researchers have shown the HICLAS approach to be related significantly to theoretically relevant variables (e.g. Robey et al, 1989;Haviland et al, 1994) and there is evidence for the structure of social selves in late adolescence (e.g. Rosenberg and Gara, 1985;Berzonsky and Neimeyer, 1988;Byrne and Shavelson, 1996); thus, these prior studies show evidence of construct validity.…”
Section: Methodsmentioning
confidence: 96%
“…The notion of superordinate selves originated with Kelly (1955), who asserted that some identities are perceived as more salient and significant to an individual than are others. As applied to HICLAS set-theoretic modeling, a self is superordinate if it is in a self-class connected to any lower level self-class (Robey et al, 1989). In applying the concept of superordinate selves to HI-CLAS self-structure, Robey et al maintained that selves which others depend upon would be perceived to be more important and salient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies have shown that paranoid patients excessively attribute negative events to external causes [1][2][3][4] particularly malevolent others [5]. This attributional bias seems to be associated with self-representations that are poorly elaborated [6] and contradictory [7]. Although simple self-esteem questionnaires have yielded inconsistent findings [1,8,9], studies using indirect measures have provided consistent evidence of substantial dissatisfaction with the self in paranoid patients.…”
Section: Introductionmentioning
confidence: 99%